Application of Symposium Discussion Method to Improve Learning Outcomes of Class X E 10 Students in PAI and Ethics Subjects at SMAN 1 Lareh Sago Halaban - Muhammad Sufyan (BiCED Proceeding, 2024)
This study aims to improve the learning outcomes of students in class X E 10 at SMAN 1 Lasahan through the application of the symposium discussion method with questioning skills in the Islamic Religious Education subject, specifically on the topic of avoiding free association behaviors based on QS. Al-Isra' 17:32. This Classroom Action Research (CAR) was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The results showed that the application of the symposium discussion method could enhance students' questioning skills and their learning outcomes. Based on data analysis, there was a significant improvement in the learning outcomes between cycle I and cycle II, with the percentage of students achieving excellent scores increasing from 13.33% in cycle I to 73.33% in cycle II. Therefore, it can be concluded that the symposium discussion method is effective in improving questioning skills and learning outcomes in the Islamic Religious Education subject at SMAN 1 Lareh.